Modern weapons and military equipment for the issue 2-2021 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Tank dreams: Mulling the future of Russian armour design conceptsElta Systems reveals new passive radarRafael demos Drone Dome-L with hard-kill laser capabilityEyes in the sky: How the Orlan-10 UAV is shaping Russian artillery operationsEDA readies smart textile for operational testingRussian army to get Sprut-SDM1 SPATG self-propelled anti-tank gun
Keywords: modern; weapons; military equipment